E-Procurement: Inovasi Pengadaan Barang dan Jasa Secara Digital di Biro Umum Bagian Rumah Tangga Sekretariat Daerah Provinsi Jawa Timur - Hafizh Akbar Dwi Krisna; Bagus Nuari Hermawan (IAI Nasional Laa Roiba Bogor, 2024)
This research aims to examine innovations in implementing policies for providing government goods and services via e-Procurement at the General Bureau of the Household Section of the Regional Secretariat of East Java Province using the George C. Edwards III approach. The method applied in this study is a descriptive qualitative research method. Data was obtained through interviews, observation and documentation. The data sources used are primary data and secondary data. The results of the research show that the General Bureau of the Household Section of the Regional Secretariat of East Java Province has quality human resources (HR) as evidenced by participation in certification and good communication between officials providing goods and services and staff providing goods and services who play a role.